Psychometric properties of the social characteristics on work design scale - Ferreira-Oliveira , Ana Teresa; Fernandes , Sara; Veloso, Ana; Proença , Teresa (Conferência - Investigação e Intervenção em Recursos Humanos, 2023)
Over the years several models for work design have been developed, however the need to understand the complexity of the social context was one of the limitations that all models have encountered. The proposal made by Morgeson and Humphrey (2006) makes relevant contributions to this approach, having social characteristics has a key component of component of work design. The aim of this paper is the adaptation of the social characteristics’ subscale of Morgeson and Humphrey's (2006) Work Design Questionnaire, to the Portuguese context. An exploratory factor analysis and confirmatory factor analysis were conducted using IBM SPSS (AMOS). Results show that the instrument has good psychometric characteristics for use in the Portuguese language and, therefore, has proven value in measuring social characteristics in work design. This instrument has practical advantages for its users as it can be used to design and/or redesign work in organizations and to conduct research regarding the nature of work and its antecedents or impacts. Future research should focus on the convergence and divergent validity of this instrument. The usefulness of designing work considering social characteristics are numerous and they focus on promoting work engagement and productivity, among others.